Hermeneutic Phenomenology: Bridging Western and Japanese Perspectives and Languages. (26th May 2022) - Doering, Keiko; McAra-Couper, Judith; Gilkison, Andrea
This article offers the reader methodological insights emerging from a hermeneutic phenomenological study that examined the meaning of the woman–midwife relationship in Japan. The methodology of hermeneutic phenomenology was chosen because it is well suited to reveal women's and midwives' lived experience that is often taken for granted in day-to-day maternity care settings. However, implementing the methodology was not without its challenges. These challenges included whether hermeneutic phenomenology, based on Western philosophy, could be appropriate for conducting a study involving a researcher and participants who identify as Japanese. Further, while the study required final write up in English, the interviews were conducted in Japanese. Utilizing hermeneutic phenomenology relies on language as the tool for accessing the phenomenon of enquiry. However, Japanese culture is less expressive and, relative to Western cultures, values non-verbal communication. Beyond verbal expression, language also conveys unique influences of each culture. Although it may be challenging to conduct research between different cultures, and their unique ways of thinking and languages, it is not an impossible situation and can be rewarding. The value of using hermeneutic phenomenology for a Japanese centered study helped to convey the meaning of the woman–midwife relationship in Japan. This article details the unique process of the study, in terms of the philosophical foundation and languages, to provide methodological insights and advances for future cross-cultural qualitative research.